Galeri Terapung yang Mengapung; Partisipasi Masyarakat Dalam Pengembangan Wisata Kampung Sasirangan Sungai Jingah Kota Banjarmasin - Muhammad Faisal; Sri Hidayah (Prodi Sosiologi FISIP ULM, 2023)
Sasirangan Sungai Jingah Village Tourism, Banjarmasin City is a tourist destination that is developing it by utilizing the potential of the river in the form of making a Floating Gallery tourist object to be used as a support for its implementation. This study aims to see how the participation of local communities in the development of Kampung Sungai Jingah Sasirangan Tourism. This study uses a qualitative descriptive approach with a qualitative research type. Data collection techniques using non-participatory observation, in-depth interviews and documentation. The results of the study showed that the participation of the people of Sasirangan Sungai Jingah Village in the development of Kampung Sasirangan Sungai Jingah Tourism were: 1) in the form of participation in planning and decision making the local community was not involved, because the community was not invited to participate in determining what their tourism needed from the existing tourism development program. have been done; 2) Then in the form of participation in the implementation of tourism development, the community is also not involved, because it is only carried out by the Banjarmasin City Tourism Office; 3) Then participation is in the form of taking benefits, the participation of the local community is not comprehensive, it is shown that the majority of the community does not use and maintain the results of the tourism development that is being carried out, only a small part can be found; 4) In the evaluation form, the community participates quite well, this is shown by the local community conducting monitoring and the local community also providing suggestions and suggestions regarding the results of the tourism development.